Family practice guidelines - Cash, Jill C. (New York, NY : Springer Publishing Company, 2024)
This bible of family practice for primary care clinicians and students provides current national practice guidelines for professional standards of care across the life span. Concise and clearly organized, this primary care resource guide features detailed, step-by-step instructions for physical examinations and diagnostic testing in the outpatient setting, information on health promotion, care guidelines, dietary information, information on culturally responsive care, patient resources, and abundant patient-education handouts. Now in color with abundant images and illustrations, this fifth edition features thoroughly updated guidelines and recommendations to reflect latest in practice, as well as many new guidelines. Each of the diagnoses includes definition, incidence, pathogenesis, predisposing factors, common complaints, signs/symptoms, subjective data, physical exam and diagnostic tests, differential diagnosis, and a care plan. (Publisher).
I. Guidelines -- 1. Health Maintenance Guidelines -- 2. Public Health Guidelines -- 3. Pain Management Guidelines -- 4. Dermatology Guidelines -- 5. Eye Guidelines -- 6. Ear Guidelines -- 7. Nasal Guidelines -- 8. Throat and Mouth Guidelines -- 9. Repiratory Guidelines -- 10. Cardiovascular Guidelines -- 11. Gastrointestinal Guidelines -- 12. Genitourinary Guidelines -- 13. Obstetrics Guidelines -- 14. Gynecological Guidelines -- 15. Sexually Transmitted infections Guidelines -- 16. Infectious Disease Guidelines -- 17. Systemic Disorders Guidelines -- 18. Musculoskeletal Guidelines -- 19. Neurological Guidelines -- 20. Endocrine Guidelines -- 21. Rheumatological Guidelines -- 22. Psychiatric Guidelines -- 23. Assessment Guide for Sport Participation -- II Procedures -- III Client Teaching Guides -- IV. Appendices
Includes bibliographical references and index.
Keywords: Diagnostic Techniques and Procedures; Family Practice; Nurse Practitioners; Physician Assistants; Primary Nursing